The Impact of Workload and Job Insecurity toward Employee Work Stress Due to Covid-19 Pandemic - Diwyarthi, Ni Desak Made Santi; Prawira, Kadek Dwika (Multidisciplinary Journal of Education , Economic and Culture, 2024)
This study aimed to investigate how job insecurity and workload, both individually and in combination, affected employee work stress at LA Hotel Seminyak during the pandemic. The data for this research were collected through various methods, including observation, interviews, documentation, and questionnaires. A total of 31 respondents participated in the study, and a saturated sampling technique was used. The data analysis involved classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and the determination of the coefficient of determination. The findings of this study revealed that job insecurity, when considered individually, had a positive and statistically significant impact on employee work stress. Similarly, workload, when examined in isolation, also had a positive and significant effect on employee work stress. When both job insecurity and workload were considered together, they collectively had a significant influence on employee work stress. The coefficient of determination test indicated that job insecurity and workload together accounted for 76.0% of the variance in work stress, while the remaining 24.0% was attributed to other variables not addressed in this study.